Peran Program Bantuan Sosial dalam Pengentasan Kemiskinan : Evaluasi Dari Berbagai Penelitian - Gracenda Febina Br Purba,; Dicky M.C. Sinulingga,; Josua Togatorop,; Lokot Muda Harahap, (Jurnal Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the impact of social assistance programs on poverty reduction in Indonesia, evaluate the effectiveness of non-cash social assistance distribution mechanisms, and identify obstacles and challenges in implementing the program to provide recommendations for improving its effectiveness. This study uses a literature study method by analyzing various relevant, trusted journals and theses published in the last five years. The results of the study show that social assistance helps increase purchasing power and access to basic services, but still faces obstacles such as inaccurate targeting, lack of transparency, and dependency of beneficiaries. In addition, weak coordination and inconsistent policy changes also hamper the effectiveness of the program. Improvements are needed in the data collection system, increased transparency, and integration of social assistance with economic empowerment programs so that recipients are more independent. With a better strategy, this program can be more effective in alleviating poverty and improving community welfare in a sustainable manner.